Aerated Concrete Produced Using Locally Available Raw Materials - Matalkah, Faris; Bharadwaj, Harsha; Balachandra, Anagi; Soroushian, Parviz (Civil Engineering Journal, 2017)
Aerated concrete materials were developed with abundant natural materials. Aerated concrete can provide insulating qualities complemented with secondary structural attributes when used as core in sandwich composites for building construction. A hybrid binder that comprised lime and gypsum was used. Different foaming agents were considered for production of aerated concrete, including saponin that is found abundantly in different plants. Different formulations were considered, and the stability of the foam structure as well as the density and early-age compressive strength of the resulting aerated concrete were evaluated. One formulation comprising lime-gypsum binder with saponin foaming agent, with a density of 0.53 g/cm3, was further characterized through performance of thermal conductivity, split tension, flexure, elastic and shear modulus and sorptivity tests. The results pointed at the satisfactory balance of qualities provided by the aerated concrete when compared with alternative aerated concrete materials.